PERAN KEGIATAN KEAGAMAAN DALAM KEBAHAGIAAN WANITA LANSIA PASCA GEMPA DI DAERAH ISTIMEWA YOGYAKARTA - AM Diponegoro, Choirul Anam (Universitas Ahmad Dahlan, 2006)
AbstractVarious services for older people in order to make them live in happiness should keep todevelop. This research tried to find out whether or not role of religious activity on older peopleslife happiness. Religious activity included religious knowledge and religious acts. Life happinessincluded affect and satisfaction on life. This research will benefit if it is found proper service inolder people to achieve life happiness.Sample was randomly obtained from praying groups in five villages and four regenciesand one city of Special Province of Yogyakarta. It was expected to be able to describe conditionin older people at Special Province of Yogyakarta. Using questionnaire and scale deliveredindividually, it was obtained data on level activity and religious knowledge and happiness from131 older women. Quantitative data analysis used canonic correlation, it will be obtainedseparated or joint correlation between two independent and dependent variable.Conclusion of this research was that there was significant role level of activity andhappiness and there was significant roel between religious knowledge level and happiness. Aswell as it could be concluded that axctive older women in religious activity were happier thanthose that has inactive religious activity.